KETERLIBATAN DAN ANTUSIASME BELAJAR SISWA SD MELALUI QUIZIZZ PAPER MODE DALAM PEMBELAJARAN BAHASA INDONESIA - Santi Dwi Agustina; Emy Yunita Rahma Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the involvement and enthusiasm of elementary schoolstudents in learning Indonesian through the implementation of Paper Mode Quizizz.The background of this research is rooted in the limited access to digital technologyin some elementary schools, which requires innovative learning media that remaininteractive even without electronic devices. The research employed a descriptivequalitative approach with fifth-grade students at an elementary school in Jombangas the subjects. Data were collected through classroom observations, interviewswith students and teachers, and documentation of learning outcomes. The datawere analyzed using the stages of data reduction, data presentation, and conclusiondrawing. The findings indicate that Paper Mode Quizizz is able to enhance studentengagement in the learning process, as reflected in their active participation,attention, and interaction during activities. Furthermore, students demonstrated highenthusiasm, expressed through positive attitudes, curiosity, and motivation tocomplete the questions competitively. Thus, Paper Mode Quizizz can be consideredas a creative, effective, and adaptive alternative learning medium to improve thequality of Indonesian language learning experiences in elementary schools.